Pengungkapan Karakter Manusia melalui Fraseologi dengan Komponen Kata Птица/Ptitsa/‘Unggas’ dalam Bahasa Rusia: Kajian Etnolinguistik - Rahmi Imanda Wildan; Susi Machdalena; Ani Rachmat (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to describe the depiction of human characters in Russian phraseology that contains the word птица/ptitsa/ 'poultry'. The study is descriptive qualitative and uses an ethnolinguistics approach to analyze the data, especially to analyze the meaning of phraseology based on the background of its appearance . The data are excerpts of sentences in novels, books, or electronic newspapers collected through the ruscorpora.ru website using the listening method with note-taking techniques. Data analysis used referential pairing method with ethnolinguistic approach. Seven phraseological data containing the words курица/kuritsa/ 'chicken', гусь/gus'/ 'black swan', лебед/lebed'/ 'white swan', and гоголь/gogol'/ 'golden-eyed duck' were found. Of the eight data obtained, seven data are phraseologies that express bad character, and one phraseology that expresses good character. The word курица/kuritsa/ 'chicken' represents a bad character in the form of a fool, someone with poor and careless writing, and someone who has no stand. The word гусь/gus'/ 'black swan' represents the character of someone who is cunning, лебед/lebed'/ 'white swan' represents the good character of loyalty and the bad character of laziness, while, the word гоголь/gogol'/ 'golden-eyed duck' represents arrogance.